Occupational Stress and Work Engagement as Predictors of Job Satisfaction among University Security Staff - Esohe Ehondor; Damilola Osuntogun; Nurudeen Ariwoola; Emmanuel Uye (LP3M INSTITUT KH YAZID KARIMULLAH, 2025)
Job satisfaction contributes to individual and organizational performance. It has been investigated using different predictors among workers in different occupations. However, studies examining job satisfaction among university security staff tend to be lacking. Therefore, this study examines the predictability of occupational stress and work engagement on job satisfaction among security staff of the University of Ibadan, Nigeria. Cross-sectional survey design was adopted while data were collected from 197 participants using validated scales. Data collected were analyzed using multiple regression to test an hypothesis which was accepted at p < .01 level of significance. The result revealed that occupational stress and work engagement jointly predicted job satisfaction among study participants [R2=.13, F(2,195) = 14.64, p <.01]. In addition, occupational stress (β=.33, p <.01) and work engagement (β = -.16, p <.01) independently predicted job satisfaction among study participants. The study concluded that occupational stress and work engagement marginally predicted job satisfaction among study participants. The implication of this finding is that security staff of the University of Ibadan are working with low job satisfaction as they experienced occupational stress and low work engagement. The study recommended that the university administrators should design and implement policies that would reduce occupational stress and increase work engagement to improve their job satisfaction